INVENTED IDENTITIES: THE INTERPLAY OF GENDER, RELIGION AND POLITICS IN INDIA. - Sabrina Alves (Último Andar)
Julia Leslie and Mary McGee (eds.), Invented identities: the interplay of gender, religion and politics in India.New Delhi: Oxford University Press. 2000. 309 pages. Rs. 495